The protective effect of 5-HT3 receptor antagonist in thyrotropin releasing hormone-induced gastric lesions - YEGEN, BERRAK (My University, 1997)
The present study examined 1) oxidative stress and gastric lesions induced by thyrotropin releasing hormone (TRH) 2) The effect of a 5-hydroxytryptamine3 (5-HT3) receptor antagonist, ICS 205930 on protective effect of calcitonin on gastric lesions produced by TRH. Calcitonin (5 micrograms/10 microliter) was injected i.c.v. 10 min before TRH (10 micrograms/10 microliter, i.c.v.) injection or ICS 0.5 mg/kg, (i.p.) was given 60 min prior to calcitonin or TRH to rats. Ulcer index, lipid peroxidation (LP) and glutathione (GSH) levels were quantified 3 h after TRH injection in the stomach, liver and brain. TRH caused mucosal lesions (UI: 10.0 +/- 2.0 mm) without changing gastric GSH and LP. JCS did not alter the protective effect of calcitonin against TRH-induced lesions but attenuated. TRH-induced lesion formation. The oxidative effects of calcitonin or ICS were similar to TRH but both drugs attenuated gastric lesion formation. Hence, oxidative changes in tissues studied are not directly involved in TRH-induced lesions.
Keywords: Female; Animals; Male; Rats; Brain; Rats, Wistar; Glutathione; Oxidative Stress; Liver; Gastric Mucosa; Stomach Ulcer; Injections, Intraventricular; Lipid Peroxides; Brain Stem; Calcitonin; Indoles; Receptors, Serotonin; Serotonin Antagonists; Thyrotropin-Releasing Hormone; Tropisetron